Value of Electrocardiogram for Identification of Localization of Ischemic Lesions and its Comparison with Coronary Angiography Results - Yıldız, Abdülmelik; Arslan, Nadi (Fırat University, 2004)
Objective: In this study, importance and utilization of electrocardiography (ECG) in identifying the location of lesions and its comparison to coronary angiography (CA) were investigated in cases with ischemic localizations determined by ECG. Sensitivity, specificity and positive predictability values, total obstructions in vessels and incidence of multiple vessel disease were also sought.Materials & Methods: A total of 101 cases (78 men, 23 women) ageing between 28 and 74 (52.1±10.9) were divided into three groups according to ECG findings. Group-I (38) included cases who had myocardial infarction in ECG, Group-II (38) having T negative and Group-III (25) with normal resting ECGs. Localizations, according to derivation in ECG were classified as I, aVL, V1-6 anterior, and II, III, aVF inferior. CA was applied after ECG recordings, >50% narrowing in the coronary artery lumen was considered to be important. Results: Narrowing in the artery responsible for lesion in the fact group-I or Group-II which had anterior or inferior localizations in ECG (LAD for anterior wall, RCA or CX for inferior wall) the sensitivity values (according to presence or absence of narrowing in CA) were found to be 71%, 63% and 56%, specificity 51%, 78%, 73% and positive predictability 50%, 58%, 43%, respectively. Comparison of narrowing in CA in Group-I showing inferior or anterior localizations showed that the total obstruction values were 60% and 18%, respectively, (P

Amaç: Bu çalışmada iskemi lokalizasyonunun elektrokardiografik (EKG) olarak belirlenen olgularda, koroner anjiyografi (KA) yapılarak her iki yöntem arasında lezyonların yerleşim yerini belirlemede EKG'nin önemi ve yararı araştırıldı. Bununla ilgili sensitivite, spesifite ve pozitif prediktivite değerleri ile damarlardaki total tıkanıklıklar ve multipl damar hastalığı insidansı da araştırıldı.Gereç ve Yöntem: Yaşları 28-74 arasında olan (52,1±10,9) 78'i erkek, 23'ü kadın 101 olgu EKG bulgularına göre 3 gruba ayrıldı. EKG'lerinde geçirilmiş miyokard infarktüsü olanlar (GMİ), Grup-1 (38 olgu), T menfiliği olanlar, Grup-2 (38 olgu) ve istirahat EKG'leri normal olanlar, Grup-3 (25 olgu). EKG'de lezyonun bulunduğu derivasyona göre lokalizasyonlar; I, aVL, V1-6 anteriyor, II, III, aVF inferiyor olarak sınıflandırıldı. EKG kayıtlarından sonra KA yapıldı. Koroner arter lumeninde %50 darlıklar önemli darlık olarak kabul edildi. Bulgular: EKG'de anteriyor veya inferiyor lokalizasyonu olan Grup-1 ve Grup-2 olgularda lezyondan sorumlu olan arterde (anteriyor bölge için LAD, inferiyor bölge için RCA veya CX) KA'da darlığa göre hesaplanan sensitivite değerleri sırasıyla %71, %63 ve %56 spesifite değerleri %51,%78, %73 ve pozitif prediktivite degerleri %50, %58, %43 olarak bulundu. KA'da bulunan darlıkların karşılaştırılmasında inferiyor ve anteriyor lokalizasyon gösteren Grup-1 olgularda damarlardaki total tıkanıklık sırasıyla %60, %18 (P
İskemik Lezyon Lokalizasyonlarının Belirlenmesinde Elektrokardiyogramın Değeri ve Koroner Anjiyografi Sonuçlarıyla Karşılaştırılması